The Role of School Principals in Improving Teacher Competency through Learning Communities in Public Special Schools Blitar City Indonesia - Khoirun Nisak; Ahsan Romadlon Junaidi; Ahmad Samawi (Universitas Negeri Malang, 2025)
This research is preliminary research on the role of school principals in improving the competency of Special School teachers through a Learning Community in one of the Special Schools in Blitar City. This research aims to determine the role of school principals in improving the competence of special school teachers through Learning Communities. This research uses a descriptive qualitative method. The subjects of the research are teachers in a Public Special School. The research is conducted in a Public Special Schools in Blitar City. The techniques used to collect data in this research are observation and documentation. The research results show that the managerial role of the school principal is a crucial element that plays the most important role in improving the competence of special school teachers. To improve the competency of special school teachers can be obtained by developing a Learning Community in the educational institution properly. The role played by the school principal is to facilitate collaborative learning about the MERDEKA curriculum, discuss and practice good practices of MERDEKA curriculum, facilitate collaboration in the development of teaching plans, learning reflections with teachers colleagues by reviewing learning modules related to rubric of assessment, problems faced in teaching learning process and the solutions taken. The Learning Community is a forum for teachers to exchange ideas and all matters related to teaching learning activities.